2013
DOI: 10.1021/ja4051108
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Catch Bonds and the Anti-Hammond Effect in Polymer Mechanochemistry

Abstract: While the field of polymer mechanochemistry has traditionally focused on the use of mechanical forces to accelerate chemical processes, theoretical considerations predict an underexplored alternative: the suppression of reactivity through mechanical perturbation. Here, we use electronic structure calculations to analyze the mechanical reactivity of six mechanophores, or chemical functionalities that respond to mechanical stress in a controlled manner. Our computational results indicate that appropriately direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
136
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(150 citation statements)
references
References 52 publications
11
136
1
2
Order By: Relevance
“…These include energy landscapes with one bound state and two unbinding pathways 43 ; an energy landscape with two bound states, one of which is preferentially stabilized by force 44,45 ; bond dissociation along a multidimensional landscape where the direction of the tensile force and the reaction coordinate are misaligned [46][47][48] ; a freeenergy landscape with dynamic disorder that thermally fluctuates with time 49,50 ; and allosteric deformation models where external force changes the structure of the receptor either directly at the ligand-binding site 51 or at a distal location that ultimately propagates the deformation to the binding pocket [52][53][54][55] . Our simulations suggest that X-dimers form catch bonds via a slidingrebinding mechanism where a pulling force flexes the ectodomain and slides opposing EC1 domains resulting in the formation of de novo, force-induced H-bonds.…”
Section: Article Nature Communications | Doi: 101038/ncomms4941mentioning
confidence: 99%
“…These include energy landscapes with one bound state and two unbinding pathways 43 ; an energy landscape with two bound states, one of which is preferentially stabilized by force 44,45 ; bond dissociation along a multidimensional landscape where the direction of the tensile force and the reaction coordinate are misaligned [46][47][48] ; a freeenergy landscape with dynamic disorder that thermally fluctuates with time 49,50 ; and allosteric deformation models where external force changes the structure of the receptor either directly at the ligand-binding site 51 or at a distal location that ultimately propagates the deformation to the binding pocket [52][53][54][55] . Our simulations suggest that X-dimers form catch bonds via a slidingrebinding mechanism where a pulling force flexes the ectodomain and slides opposing EC1 domains resulting in the formation of de novo, force-induced H-bonds.…”
Section: Article Nature Communications | Doi: 101038/ncomms4941mentioning
confidence: 99%
“…Indeed, an analysis of all possible pulling scenarios involving pairs of pulling points and applied to 6 known mechanophores showed that the compliance χ TS is positive for all of them. 4 We note, however, that, for highly symmetric molecules, the alignment between the pulling direction and the steepest descent coordinate may result from symmetry.…”
Section: One-dimensional Models Of Mechanochemistry Will Almost Almentioning
confidence: 74%
“…Contrary to the theoretical arguments presented above and despite computational evidence of multidimensional effects, 4,[73][74][75][76] one-dimensional models are widely used to (successfully) fit single-molecule force spectroscopy data, with experimental evidence of multidimensional behavior limited to only a handful of reports.…”
Section: If One-dimensional Models Fail Why Do They Fit Experimementioning
confidence: 99%
See 2 more Smart Citations